MENINGKATKAN HASIL BELAJAR SISWA TENTANG MENENTUKAN NILAI FPB DAN KPK DUA BILANGAN ATAU LEBIH MENGUNAKAN METODE MAKE A MACHT PADA MATA PELAJARAN MATEMATIKA KELAS VI SEMESTER 1 SDN PESAREAN 01 TAHUN PELAJARAN 2017/2018: Array - Wuryaningsih, Sri (Universitas Peradaban, 2019)
The purpose of this research was to improve student learning outcomes in determining the FPB and KPK values ​​of two or more numbers through the learning model make a macht. The research subjects were class VI students at Pesarean State Elementary School 01, Pagerbarang Subdistrict with 33 students consisting of 18 male students and 15 female students. The method of data collection in this research is documentation, observation, and tests. This research was carried out with the design of Classroom Action Research (CAR). The results showed that the learning model of make a macht can improve student learning outcomes in determining the value of FPB and KPK two or more numbers.